1977
DOI: 10.1021/ic50176a040
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal-nucleoside interactions. 10. Binding of cis-diammineplatinum(II) to cytidine and uridine in aqueous solution: necessary conditions for formation of platinum-uridine "blues"

Abstract: Both cytidine and uridine react with (H3N)2Ptn and enPt11 in aqueous solution over a wide pH range. The reactions with cytidine are complete within a few hours, while those with uridine are considerably slower. In both cases mono and bis complexes are formed. In acidic solution, (H3N)2Ptn behaves as a bifunctional electrophile toward cytidine, while at pH 7 it acts as a unifunctional electrophile. The equilibrium constant for [(H3N)2Pt(OH2)2]2+ + Cyd <=± [(H3N)2PtCyd(OH2)]2+ + H20 was estimated from Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 12 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…It is likely that both platinum atoms are bound to the same types of ligands through N(3) of cytosine and Notizen cytidine, resp., although no nitrogen hf coupling can be resolved. The complexes are formed at a pH value, where usually bis-complexes are found after short reaction times [4], Therefore, the ESR spectrum shown in Fig. 1 might be attributed tentatively to a binuclear platinum complex, with each of the platinum centers bound to two cytosine or cytidine molecules.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is likely that both platinum atoms are bound to the same types of ligands through N(3) of cytosine and Notizen cytidine, resp., although no nitrogen hf coupling can be resolved. The complexes are formed at a pH value, where usually bis-complexes are found after short reaction times [4], Therefore, the ESR spectrum shown in Fig. 1 might be attributed tentatively to a binuclear platinum complex, with each of the platinum centers bound to two cytosine or cytidine molecules.…”
Section: Resultsmentioning
confidence: 95%
“…Concerning its interaction with cytosine and cytidine it is known that bis complexes are formed in the pH range 3-5.5 whereas mono complexes occur in the pH range 5.5-8.5. The binding site is the N(3) nitrogen [4]. These results have been obtained with solutions containing 25 mM of c/s-diaquodiammineplatinum-(II), an hydrolysis product of c?s-PDD, and 50 mM of cytidine reacting at 25 c C. Under different experimental conditions, e.g.…”
Section: Cis-dichlorodiammineplatinum(ii)mentioning
confidence: 95%
“…It is known that the N(3) and the C=O group in cytosine have deep potential minima for the interaction with an external point charge. 27 With cytidine, it has been reported that hard metal ions bind to the C=O group whereas soft metals such as silver bind to N(3), in general. From X-ray crystallographic studies, 28 1methylcytosine, was found to bind to Pt via N(3) and to Ag through N(3) and C=O.…”
Section: Resultsmentioning
confidence: 99%
“…The order of reactivity of the four nucleotides with cisplatin was established as GMP > AMP >> CMP > UMP/TMP by Raman difference spectrophotometry [11]. Although it seemed that pyrimidine nucleobases have low reactivity to cisplatin, numerous studies have demonstrated the existence of “platinum pyrimidine blues” obtained from reactions of cisplatin and pyrimidine nucleobases such as uracil, 1-methyluracil, thymine, 1-methylthymine, uridine, and thymidine [12,13,14,15,16]. Moreover, Tobias et al, using Raman plus 1 H-NMR and 13 C-NMR spectroscopy, observed the coordination of cis -[(NH 3 ) 2 Pt(H 2 O) 2 ] 2+ to cytidine-N(3) and the deprotonated uridine-N(3) [14].…”
Section: Introductionmentioning
confidence: 99%